Apology Strategies Used by Students in University of Balikpapan - retnowaty retnowaty; Nurliani Maulida (Journal of English Language Studies, 2019)
There are two objectives of the study namely to investigate kind of apology strategies are used by students in University of Balikpapan and to investigate how age and social status affect their choice of apology strategies. The design of this study is descriptive qualitative. Instrument to collect the data was DCT task devised by Hasan in 2014. The data were analyzed and categorized by using theory of Trosborg and Aijmer compiled by Firiani & Lestari in Fitriani (2012). Findings have shown that an overwhelming majority of the apologies were combinations rather than single type. The most often used combined strategies by students in University of Balikpapan were ‘explicitly apologizing + acknowledging responsibility + offering redress’. Moreover, it can be inferred that age and social status affected participants’ choice of apology strategies since the result of this study showed that they had different combined apology strategies based on older, younger, same age and higher, lower, equal social status.